The Transformation of Tĕhôm : From Deified Power to Demonized Abyss - Lu, Rosanna A. (Biblical Interpretation Series, 2025)
Tehom, the Hebrew Bible's primeval deep, is a powerful concept often overlooked outside of creation and conflict contexts. Primeval waters mark the boundary between life and death in the Hebrew Bible and the ancient Near East, representing the duality of both deliverance and judgment. This book examines all contexts of Tehom to explain its conceptual forms and use as a proper noun. Comparative methodology combined with affect and spatial theories provide new ways to understand how religious communities repurposed Tehom. These interpretations of Tehom empower resilience in times of suffering and oppression.